The Accommodation of Social and Cultural Forces in the Decision-making Process by Judges In Indonesia - Ade Saptomo (Lex Publica, 2019)
This paper aims to explain the accommodation of social and cultural forces in the legal verdict-making process by judges in Indonesia. A good legal verdict is a legal decision resulting from structural interactions between the arguments of attorneys, lawyers, advocates, witnesses, expert testimonies, and other parties regulated in certain Acts related to the legal cases filed in the court. However, the good process of social interaction requires the accommodation of social forces (social value) and cultural forces (cultural value) of the community where the case occurs. Lately, the response has developed in the midst of a society where the legal verdict by judges in Indonesia does not reflect justice. Justice in society can only be fulfilled in the legal verdict-making process. The question to be asked is whether or not the judge discovers the legal values implemented in society. Discovering the legal values that live in such a society in accordance with legal and normative theories is also regulated in Article 5, paragraph 1 of Judicial Power Act No. 48/2004. Abstrak Tulisan ini bertujuan untuk menjelaskan akomodasi kekuatan sosial dan budaya dalam proses pengambilan keputusan hukum oleh hakim di Indonesia. Putusan hukum yang baik adalah putusan hukum yang dihasilkan dari interaksi struktural antara dalil-dalil para kuasa hukum, advokat, advokat, saksi, keterangan ahli, dan pihak-pihak lain yang diatur dalam undang-undang tertentu yang berkaitan dengan perkara hukum yang diajukan di pengadilan. Akan tetapi, proses interaksi sosial yang baik memerlukan akomodasi kekuatan sosial (social value) dan kekuatan budaya (cultural value) masyarakat di mana kasus tersebut terjadi. Belakangan ini, respon berkembang di tengah masyarakat dimana putusan hukum oleh hakim di Indonesia tidak mencerminkan keadilan. Keadilan dalam masyarakat hanya dapat dipenuhi dalam proses pengambilan keputusan hukum. Pertanyaan yang harus diajukan adalah apakah hakim menemukan atau tidak nilai-nilai hukum yang berlaku dalam masyarakat. Menemukan nilai-nilai hukum yang hidup dalam masyarakat tersebut sesuai dengan teori-teori hukum dan normatif juga diatur dalam Pasal 5 ayat 1 UU Kekuasaan Kehakiman No. 48 Tahun 2004. Kata kunci: Kekuatan sosial dan budaya, Hakim, Putusan pengadilan